"It does not mean that they cannot do mathematics”: Beliefs about mathematics learning difficulties - Hamukwaya Shemunyenge Taleiko; Haser Çiğdem (Modestum, 2025)
Namibian preservice high school mathematics teachers’ (N=4) and teacher educators’ (N=3) beliefs about mathematics learning difficulties (MLD) were investigated to document the beliefs developed at the end of the teacher education program, the views and practices that might be emphasized in the program, and possible changes in these beliefs during the first year teaching. Preservice teachers were interviewed before they graduated from the teacher education program and during their first-year teaching. Teacher educators were interviewed once. Participants believed that the most important factor causing MLD at the high school was students’ knowledge and beliefs. Teacher educators stated former unqualified teachers and preservice teachers stated curriculum and teachers’ workload as other causes of MLD. Participants suggested individual support and mixed ability grouping to reduce students’ MLD. The partial alignment of beliefs among the participants showed that preservice teachers might have developed some beliefs through the views and practices emphasized in the program. Preservice teachers elaborated more on MLD when they became teachers and stated similar beliefs with some stress on their MLD-related practices. Preservice teachers did not comment on how teachers’ knowledge and practices might influence students’ MLD in both times. Findings pointed that teacher education programs should focus on increasing preservice teachers’ awareness of how their knowledge, practices and beliefs about MLD might affect students to improve their future practices. It is possible that teachers’ beliefs about MLD could be related to their beliefs about the nature of mathematical knowledge and indicators of high performance in mathematics.